Biomimetics in drug delivery systems: A critical review - Sheikhpour, Mojgan; Barani, Leila; Kasaeian, Alibakhsh (Journal of controlled release, 2017)
Today, the advanced drug delivery systems have been focused on targeted drug delivery fields. The novel drug delivery is involved with the improvement of the capacity of drug loading in drug carriers, cellular uptake of drug carriers, and the sustained release of drugs within target cells. In this review, six groups of therapeutic drug carriers including biomimetic hydrogels, biomimetic micelles, biomimetic liposomes, biomimetic dendrimers, biomimetic polymeric carriers and biomimetic nanostructures, are studied. The subject takes advantage of the biomimetic methods of productions or the biomimetic techniques for the surface modifications, similar to what accrues in natural cells. Moreover, the effects of these biomimetic approaches for promoting the drug efficiency in targeted drug delivery are visible. The study demonstrates that the fabrication of biomimetic nanocomposite drug carriers could noticeably promote the efficiency of drugs in targeted drug delivery systems. A general schematic of a biomimetic drug carrier. [Display omitted]